2022
DOI: 10.1002/acn3.51667
|View full text |Cite
|
Sign up to set email alerts
|

Mexiletine in spinal and bulbar muscular atrophy: a randomized controlled trial

Abstract: Objective: Patients with spinal and bulbar muscular atrophy (SBMA) often experience muscular weakness under cold exposure. Methods: In our previously conducted observational study, we assessed nerve conduction and grip strength to examine the effect of cold exposure on motor function, based on which we conducted a randomized controlled trial to evaluate the efficacy and safety of mexiletine hydrochloride in SBMA (MEXPRESS). Results: In the observational study, 51 consecutive patients with SBMA and 18 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Studies on ALS patients have shown that persistent sodium conductance is strongly associated with shorter survival, suggesting that alterations in cell excitability are pathogenic (Kanai et al , 2012). Altogether, our results suggest that the sodium current is disrupted by OLs, which is in line with the observed benefit of mexiletine, a sodium channel blocker, in patients with SBMA (Yamada et al , 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Studies on ALS patients have shown that persistent sodium conductance is strongly associated with shorter survival, suggesting that alterations in cell excitability are pathogenic (Kanai et al , 2012). Altogether, our results suggest that the sodium current is disrupted by OLs, which is in line with the observed benefit of mexiletine, a sodium channel blocker, in patients with SBMA (Yamada et al , 2022).…”
Section: Discussionsupporting
confidence: 88%
“…It has been hypothesized that this is linked to sodium channel dysfunction in skeletal muscles [ 101 ]. Yamada et al [ 49 ] conducted an observational study on 51 SBMA patients and noticed that ulnar nerve distal latency was prolonged under cold exposure compared to healthy controls ( p < 0.001), and this was correlated with grip strength. They then conducted a randomized, placebo-controlled, double-blind study on 20 subjects over 4 weeks to evaluate mexiletine hydrochloride.…”
Section: Resultsmentioning
confidence: 99%